The Fluidity of Lewoh Traditional African beliefs and Western Catholic Beliefs: A Study of John Nkemngong Nkengasong's God was African (London Journal of Research In Humanities and Social Sciences, 2025)
The paper, The fluidity of Lewoh traditional African beliefs and Western Catholic beliefs: A study of John Nkemngong Nkengasongs God was African seeks to juxtapose the similarities and differences in the traditional Lewoh African beliefs and the Western Catholic beliefs as portrayed in the selected text. The main character in the text seems to find himself at crossroads with making a choice between their traditional Lewoh beliefs and practices and their Western Catholic beliefs. Having been exposed to both belief systems from home and at school, the protagonist find shimself in a dilemma as to which of the belief systems to adhere to principally. Is any belief system actually superior to the other or better than the other? This study is based on the proposition that none of the belief systems is better than the other as much similarity abounds between the two systems in question. The study concludes that all the belief systems are geared towards the worship of an Omnipotent God based on the religious context of the believers. The author, therefore advocates for hybridized characters who understand and embrace the Lewoh and Catholic beliefs based on the context in which they find themselves. This study will employ the theories of Trans-Deconstruction: Theory on Monism and Theory of Interpretation as propounded by Pramod Ambadasrao Pawar.
Keywords: Phenomenology; ASD; late modernity; complex phenomenon; psychotherapeutic discourse; medical discourse; psychotherapeutic discourse integrated into fiction; conceptual metaphor in therapy; agent and client of psychotherapeutic discourse; language representation of feelings and emotions.; existential psychoanalysis; Phenomenological clinic; Environmental devastation; Patriarchal Categories; Ecological Problem; Vandana Shiva.; distributive law; the right to deferred exchange; capital; the triad; the riddle of Varys; terminology; term; graded series of terms; graduality; terminological gradation.; language; Culture; linguistic sign; culturalization.; Power; Deconstruction; alterity; Fluidity; Beliefs